Konseling SD Negeri dalam Rangka Pencegahan Diare pada Anak untuk Hidup Sehat dan Bahagia di Kabupaten Maros - Saide, Rusnaeni; Idris, Idris; Nawangwulan, Kurniawati; Yusfik, Yusnita; Djunaedi, Djunaedi; Jamin, Nunung Suryana (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The government program launched on Clean and Healthy Living Behavior is a collection of behaviors practiced by school residents and the school community on the basis of awareness as a result of learning. This aims to change the unhealthy behavior of school residents and the school community to become healthy. Where diarrhea is a condition characterized by increased frequency and decreased consistency of defecation. Diarrhea is often experienced by school children due to the behavior of children who do not understand about clean and healthy living. Several factors that cause diarrhea are caused by bacteria through contamination of food and drink contaminated with feces and/or direct contact with sufferers. Apart from that, the most dominant factors contributing to diarrheal diseases are water, sanitation hygiene, family latrines and water. Distance to drinking water sources, availability and ownership of toilets are risk factors for causing diarrhea. It is hoped that there will be changes in the clean and healthy living behavior of school residents and unhealthy school environment communities so that they become healthy. This service aims to find out and analyze the determinants of diarrhea in children at SDN Maros Regency. This service was carried out using survey and interview methods among residents of SDN Maros Regency with a total of 61 participants. The results of this service showed that the participants were very enthusiastic at all stages of this activity, starting from the interview stage (pre-test) which showed that the participants did not fully know about preventing diarrhea. One proof of the success of this activity is seen from the post-test results, on average students answered questions related to preventing diarrhea correctly. This shows that there has been an increase in students' knowledge about diarrhea compared to when there was no explanation about diarrhea in children.